PENGARUH KOMPETENSI KERJA DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PERSONEL POLRI PADA SEKOLAH POLISI WANITA (SEPOLWAN) DI JAKARTA - Prasetya, Richie; Nurakhim, Bambang (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This competence is an ability or capacity of a person in carrying out various tasks in a job. The work environment is something that exists around the environment of workers that can influence them in carrying out tasks such as. Work motivation is the driving force for a person to make the greatest contribution for the success of the agency in achieving its goals. The objectives of the study are as follows: To find out whether together the influence of Work Competence and Work Environment on Work Motivation of Police Personnel at the Women's Police School (Sepolwan) in Jakarta. The sampling technique used in this study the author used the Random Sampling technique or randomly from the existing population of 181 people, the population used as a sample refers to the Slovin formula in Husein Umar, 2017, 65 samples were obtained. The results of the study showed that partially and simultaneously there was a positive and significant influence between Work Competence and Work Environment on the Work Motivation of Police Personnel.